Implementasi Metode AHP dan VIKOR untuk Sistem Pendukung Keputusan PHK - Ida Bagus Gede Basudewa Weda; Ngurah Agus Sanjaya ER (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
Employee termination, or Pemutusan Hubungan Kerja (PHK) in Indonesian, is a complex and sensitive process that profoundly affects both employees and companies. While necessary for organizational viability, terminations can have adverse effects on employees, including unemployment and emotional distress. Hence, it is crucial to approach termination decisions objectively. This study implements the Analytical Hierarchy Process (AHP) and Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methodologies within a decision support system framework for PHK. AHP facilitates criterion weighting, while VIKOR aids in alternative ranking. Using employee datasets from Kaggle, AHP determines criterion importance, while VIKOR assesses employee ranking based on diverse criteria. The method successfully ranks the alternatives based on the labels. The values v=0 has the lowest termination percentage 5,6% at Q2 and v=0,75 has the highest termination percentage 98%. The implementation aims to provide insights for readers and support companies in making objective termination decisions.